Hexaphyrin as a Potential Theranostic Dye for Photothermal Therapy and 19F Magnetic Resonance Imaging. (24th March 2017) - Higashino, Tomohiro; Nakatsuji, Hirotaka; Fukuda, Ryosuke; Okamoto, Haruki; Imai, Hirohiko; Matsuda, Tetsuya; Tochio, Hidehito; Shirakawa, Masahiro; Tkachenko, Nikolai V.; Hashida, Mitsuru; Murakami, Tatsuya; Imahori, Hiroshi
Abstract: Two features of meso ‐Aryl‐substituted expanded porphyrins suggest suitability as theranostic agents. They have excellent absorption in near infrared (NIR) region, and they offer the possibility of introduction of multiple fluorine atoms at structurally equivalent positions. Here, hexaphyrin (hexa) was synthesized from 2, 6‐bis(trifluoromethyl)‐4‐formyl benzoate and pyrrole and evaluated as a novel expanded porphyrin with the above features. Under NIR illumination hexa showed intense photothermal and weak photodynamic effects, which were most likely due to its low excited states, close to singlet oxygen. The sustained photothermal effect caused ablation of cancer cells more effectively than the photodynamic effect of indocyanine green (a clinical dye). In addition, hexa showed potential for use in the visualization of tumors by 19 F magnetic resonance imaging (MRI), because of the multiple fluorine atoms. Our results strongly support the utility of expanded porphyrins as theranostic agents in both photothermal therapy and 19 F MRI. Abstract : meso ‐Aryl‐substituted expanded porphyrins have two key features as potential theranostic agents: excellent NIR absorption and the possibility for the introduction of multiple fluorine atoms at the meso ‐aryl groups. Hexaphyrin exhibited an intense photothermal effect and potential for use in visualization by 19 F MRI. These results shed light on the utility of expanded porphyrins as theranostic agents.